The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12887-020-02314-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of using hypertonic saline for nebulizing treatment in children with bronchiolitis: a meta-analysis of randomized controlled trials

Abstract: Background Inhaled hypertonic saline (HS) has shown benefit in decreasing airway edema in acute bronchiolitis which is the most common lower respiratory infection resulting in dyspnea among infants under 2 years old. The aim of this systematic review and meta-analysis was to evaluate the efficacy and safety of HS in the implementation of treatment with nebulized HS among children with bronchiolitis. Methods A systematic literature se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 56 publications
1
17
0
3
Order By: Relevance
“…However, controversial data supports the use of the hypertonic saline solution in infants with bronchiolitis. While several RCTs enrolling patients with moderateto-severe bronchiolitis showed that the administration of nebulized hypertonic saline solution, alone or in addition to other therapies, did not provide any clinical benefit and rather caused more frequently mild adverse events [74][75][76][77][78][79], other RCTs and systematic reviews reported that nebulized 3% hypertonic solution appeared safe and more effective in improving clinical severity compared to 0.9% saline solution [80][81][82][83][84][85].…”
Section: Evidence Is Equivocal For Which Treatment?mentioning
confidence: 99%
“…However, controversial data supports the use of the hypertonic saline solution in infants with bronchiolitis. While several RCTs enrolling patients with moderateto-severe bronchiolitis showed that the administration of nebulized hypertonic saline solution, alone or in addition to other therapies, did not provide any clinical benefit and rather caused more frequently mild adverse events [74][75][76][77][78][79], other RCTs and systematic reviews reported that nebulized 3% hypertonic solution appeared safe and more effective in improving clinical severity compared to 0.9% saline solution [80][81][82][83][84][85].…”
Section: Evidence Is Equivocal For Which Treatment?mentioning
confidence: 99%
“…Thể tích nước muối được lựa chọn là 4 ml là phù hợp với nhiều nghiên cứu khác trên thế giới. Tác giả Chia-Wen Hsieh [3] thực hiện nghiên cứu tổng hợp trên 4168 trẻ trong 32 nghiên cứu RCT cho thấy thể tích nước muối được lựa chọn là từ 2,5ml tới 5m. Trong đó, mứ thể tích 4m chiếm đa số với tỷ lệ gặp 19 trên 32 nghiên cứu.…”
Section: Bàn Luậnunclassified
“…1,3,6 Backbone of treatment is still supportive care with adequate hydration and oxygen inhalation to maintain normal saturation, with no defined role of antibiotics, steroids, and bronchodilator while few studies are favouring use of hypertonic saline in bronchiolitis by decline in duration of hospital stay and oxygen inhalation, whereas some other studies are reporting equivocal response with hypertonic saline and conventional therapy. [7][8][9][10][11] This study was conducted to assess the impact of nebulization with hypertonic saline (HS) i.e. 4 As per sample size, sixty pediatric patients accomplishing the inclusion and exclusion criteria were included in the study and were randomly divided into two groups by lottery method.…”
Section: Introductionmentioning
confidence: 99%